Extremophilic Natrinema versiforme Against Pseudomonas aeruginosa Quorum Sensing and Biofilm - Başaran, Tunahan Irmak; Berber, Didem; Gökalsın, Barış; Tramice, Annabella; Tommonaro, Giuseppina; Abbamondi, Gennaro Roberto; Erginer Hasköylü, Merve; Toksoy Öner, Ebru; Iodice, Carmine; Sesal, Nüzhet Cenk (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa is an opportunistic pathogen that causes high morbidity and mortality rates due to its biofilm form. Biofilm formation is regulated via quorum sensing (QS) mechanism and provides up to 1000 times more resistance against conventional antibiotics. QS related genes are expressed according to bacterial population density via signal molecules. QS inhibitors (QSIs) from natural sources are widely studied evaluating various extracts from extreme environments. It is suggested that extremely halophilic Archaea may also produce QSI compounds. For this purpose, we tested QS inhibitory potentials of ethyl acetate extracts from cell free supernatants and cells of Natrinema versiforme against QS and biofilm formation of P. aeruginosa. To observe QS inhibition, all extracts were tested on P. aeruginosa lasB-gfp, rhlA-gfp, and pqsA-gfp biosensor strains and biofilm inhibition was studied using P. aeruginosa PAO1. According to our results, QS inhibition ratios of cell free supernatant extract (CFSE) were higher than cell extract (CE) on las system, whereas CE was more effective on rhl system. In addition, anti-biofilm effect of CFSE was higher than CE. Structural analysis revealed that the most abundant compound in the extracts was trans 4-(2-carboxy-vinyl) benzoic acid.